Full-dose versus reduced-dose comparison of direct oral anticoagulants for extended treatment of venous thromboembolism: a systematic review and meta-analysis of randomized controlled trials - Zhang, Renshu; Wang, Rui; Li, Yun; Tian, Wenqi; Niu, Dandan; Cheng, Wencong; Niu, Xiaofang (Frontiers in Pharmacology, 2025)
BackgroundFor patients requiring extended anticoagulation therapy, clinicians often prescribe reduced-dose direct oral anticoagulants (DOACs) rather than full-dose, which may be related to concerns about the higher bleeding risk associated with full-dose DOACs, despite potentially better efficacy in preventing VTE recurrence. This meta-analysis aims to evaluate the net clinical benefit of reduced-dose DOACs versus full-dose DOACs in extended anticoagulation therapy.MethodsThis study has been registered in the International Prospective Register of Systematic Reviews (PROSPERO identifier: CRD420251089110). A systematic search was conducted in the PubMed, Embase, and Web of Science databases from their inception to 30 June 2025. Data extraction was done independently and in duplicate. A random-effects meta-analysis model was used to report the pooled treatment effects and 95% confidence intervals.ResultsA total of 5 randomized clinical trials were included (8,781 cases). Compared with full-dose DOAC, reduced-dose DOAC did not significantly increase the risk of recurrent VTE or death [(RR, 0.94 (95% CI, 0.68–1.29)), (RR, 0.84 (95% CI, 0.65–1.09))], but significantly reduced the risk of major bleeding/CRNMB (RR, 0.71 (95% CI, 0.61–0.82)). In the analysis of DOAC drugs, the prospective estimates for recurrent VTE were as follows: apixaban, RR, 0.93 (95% CI, 0.63–1.37); rivaroxaban, RR 0.96 (95% CI, 0.54–1.69). The prospective estimates for major bleeding/CRNMB were as follows: apixaban, RR, 0.74 (95% CI, 0.63–0.89); rivaroxaban, RR, 0.63 (95% CI, 0.48–0.84). Most findings were consistent within subgroups.ConclusionReduced-dose DOACs were associated with a significant decrease in the risk of major bleeding/CRNMB compared with full-dose DOACs, but were not associated with a significant increase in the risk of recurrent VTE. These findings support the net clinical benefit of reduced-dose DOACs compared with full-dose DOACs and reinforce adherence with current VTE guidelines.Systematic Review RegistrationIdentifier CRD420251089110.